2003
DOI: 10.1177/089686080302300208
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with a New Bicarbonate (25 Mmol/L)/Lactate (10 Mmol/L) Peritoneal Dialysis Solution

Abstract: Objective Physiological bicarbonate/lactate-based solutions may correct acidosis in a better way than standard lactate-based solutions. In this study, a new 25 mmol/L bicarbonate/10 mmol/L lactate peritoneal dialysis (PD) solution was compared with a standard 35 mmol/L lactate solution. Design This was a prospective open label study. All patients had a 2-week baseline period using the standard lactate solution, followed by 8 weeks on the bicarbonate/lactate solution and 2 weeks on the lactate-basedsolution. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…The serum bicarbonate level and pH decreased with use of the bicarbonate/lactate‐buffered neutral PDF, and the former fall within reference interval and the latter were maintained at the physiologic level during the study period. It previously demonstrated that serum bicarbonate level rose by 1.5 mEq/L when patients were switched from a 35 mEq/L lactate PDF to a 25 mEq/L bicarbonate/10 mEq/L lactate mixed PDF (total buffer 35 mEq/L) , but in the present study the buffer was decreased from a 40 mEq/L lactate to a 25 mEq/L bicarbonate/10 mEq/L lactate (total 35 mEq/L) and therefore serum bicarbonate level might decreased. Additionally, the serum lactate level and anion gap did not change.…”
Section: Discussionmentioning
confidence: 99%
“…The serum bicarbonate level and pH decreased with use of the bicarbonate/lactate‐buffered neutral PDF, and the former fall within reference interval and the latter were maintained at the physiologic level during the study period. It previously demonstrated that serum bicarbonate level rose by 1.5 mEq/L when patients were switched from a 35 mEq/L lactate PDF to a 25 mEq/L bicarbonate/10 mEq/L lactate mixed PDF (total buffer 35 mEq/L) , but in the present study the buffer was decreased from a 40 mEq/L lactate to a 25 mEq/L bicarbonate/10 mEq/L lactate (total 35 mEq/L) and therefore serum bicarbonate level might decreased. Additionally, the serum lactate level and anion gap did not change.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies with newer, biocompatible PD solutions showed no advantage over conventional solutions in relation to peritoneal membrane transport. 80,81,88…”
Section: Preservation Of the Peritoneal Membranementioning
confidence: 99%
“…This important association was stronger in patients with longer dialysis vintage, suggesting cumulative harm over extended exposure, a finding of direct relevance to Japanese dialysis populations given their longevity. Overall, it seems appropriate to avoid chronic alkalosis from over-correction by the high alkaline content of PDF, and individualize PDFs to provide appropriate alkaline content as appropriate [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%